PERAN KECERDASAN BUATAN DALAM PENDIDIKAN INKLUSIF DAN BERKELANJUTAN - NASIHUDDIN, M. (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2025)
This study examines the growing role of artificial intelligence (AI) in education, particularly in supporting personalized learning, improving access for students with special needs, and strengthening sustainable education, despite challenges related to infrastructure, digital gaps, and ethical issues. The aim of this research is to analyze how AI contributes to the realization of inclusive and sustainable education. The method used is library research, focusing on academic literature such as books, journals, and scientific reports. Data were analyzed using content analysis to identify themes, patterns, and conceptual relationships. The findings reveal that AI has significant potential to enhance inclusivity and sustainability in education, yet its implementation requires strong policy support, adequate infrastructure, and teacher competence to ensure its benefits are fully realized.